2016
DOI: 10.3390/met6010011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Loading Rate on the Hydrogen-Assisted Micro-Damage in Bluntly Notched Samples of Pearlitic Steel

Abstract: Abstract:The influence of loading rate (crosshead speed) on the fracture process of bluntly notched samples of pearlitic steel under hydrogen environment is analyzed in this paper. Results indicate that the location of the zone where fracture initiates (fracture process zone) in pearlitic steel samples with a blunt notch directly depends on the loading rate or crosshead speed. For slow testing rates, such a zone is placed in the specimen center due to hydrogen diffusion towards the prospective fracture places … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The literature survey revealed that the research in the HE of metallic materials is focused on analyzing the HE susceptibility in terms of (i) test results (macroscopic level): time to fracture in FIP test [24], fracture load in CERT tests [27][28][29]33,[36][37][38], and geometry of the test samples [10,[32][33][34][35]38], or (ii) HE damage zones (microscopic level): TTS fracture zones [16][17][18][19] and evolution of damage zones [20][21][22][23]. A key issue in this field is the selec-tion of the most adequate round-notch geometry to be used for testing the HE susceptibility of steels.…”
Section: Research Gaps Based On Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature survey revealed that the research in the HE of metallic materials is focused on analyzing the HE susceptibility in terms of (i) test results (macroscopic level): time to fracture in FIP test [24], fracture load in CERT tests [27][28][29]33,[36][37][38], and geometry of the test samples [10,[32][33][34][35]38], or (ii) HE damage zones (microscopic level): TTS fracture zones [16][17][18][19] and evolution of damage zones [20][21][22][23]. A key issue in this field is the selec-tion of the most adequate round-notch geometry to be used for testing the HE susceptibility of steels.…”
Section: Research Gaps Based On Literature Reviewmentioning
confidence: 99%
“…The HE susceptibility is obtained by comparing the measurements taken during and after the test with similar data obtained in an inert environment [27]. The crosshead speed influence was studied in [28] and the influence of the loading rate on HAMD was analyzed in [29]. In recent times, diverse test methods for evaluating HE susceptibility were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the ductility increased by as much as 60% when the loading speed increased from 7.6 × 10 −6 m/s to 4.2 m/s. Toribo et al [24] analyzed the influence of loading rate on the fracture process of bluntly notched specimens of pearlitic steel under a hydrogen environment. Results indicate that the location of the fracture zone directly depends on the loading rate.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of such changes revealed a progressive increment of the microstructural anisotropy as the drawing degree is increased. These microstructural changes also affect the macroscopic mechanical behavior of the material [20][21][22], as in their fatigue and fracture behavior [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%